The big book of hacks (Weldon Owen, 2012)
Fire up your soldering iron and get ready to hack! The ingenious projects in this book are perfect for aspiring DIY-ers, from improvising a fisheye lens for your camera or an automatic cat feeder to a solar-powered backpack to keep your gadgets charged, you'll find over 200 ideas to get your geek on!